2013
DOI: 10.1186/1742-4755-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sexual abstinence among Wolaita Sodo University Students, South Ethiopia

Abstract: BackgroundIt is over 30 years since the first case of AIDS [Acquired Immune Deficiency Syndrome] was identified. Attention has been focused recently on the promotion of the “ABCs” of HIV prevention (being abstinent or delaying sex, remaining faithful to one sexual partner, and using condoms consistently during sexual intercourse). As programs that focus on ABCs to prevent heterosexual transmission HIV are rolled out, questions of how well university students who come from varied cultural contexts actually unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
2
20
1
Order By: Relevance
“…Studies indicated that age (8), using social media (9,10) and being male (11,12) were predictors of premarital sex. Other studies indicated that onset of sexual activity is accocaited with alcohol use (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicated that age (8), using social media (9,10) and being male (11,12) were predictors of premarital sex. Other studies indicated that onset of sexual activity is accocaited with alcohol use (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated that onset of sexual activity is accocaited with alcohol use (13,14). Comprehensive knowledge of HIV/AIDS was an inconsistent predictor of premarital sex (12,15). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Gonder University, 23% of university students had reported sexual contact with prostitutes and only 37.1% of them used condom. In a study conducted in Wolaita Sodo University, 97.3% of students had good knowledge on HIV/AIDS [18-21]. …”
Section: Introductionmentioning
confidence: 99%
“…Communication practice on SRH issues = Students who discussed at least one SRH issues in the last 12 months of the study period [37].…”
Section: Operational Definitionmentioning
confidence: 99%